A hedonic valuation in Putrajaya Wetlands - A. S., Nur Syafiqah; Abdul Samad @ Iammi, Abdul Rahim; Abdul Jakit, Fathin Hanani; S., Nur Fatihah (Journal of Tourism, Hospitality and Environment Management, 2017)
This study is designed to estimate the economic value of green spaces in the land of Putrajaya by using the Hedonic Pricing Method (HPM). Economic valuation regarding green spaces in Putrajaya is targeted to give an efficient solution in investment and also to facilitate the residents of Putrajaya upon the value of the environment that they received and the significance of reserving the great environment for future consumptions. Survey questionnaires were distributed to 415 respondents in Putrajaya Wetlands who lived in the housing area 2-15 Km from this park. A Hedonic Pricing Model is developed by taking housing price as the dependent variable and structural of the house including distance to the green area as the independent variables. Housing price is used as a proxy to quantify the economic value of green space. Two models (linear model and semi-log model) mainly based on hedonic price model are formulated and regressed through ordinary least square (OLS) method. In term of model comparison, the result revealed that semi-log model (Model 2) performed better than the linear model (Model 1). As expected, a significant inverse relationship between the housing price and its distance from the residential area and the Putrajaya Wetland has been found whereby a slight decrease of 1 Km of the distance will positively increase the housing price by 5.9%. The result positively shows that the green space has contributed indirectly towards the housing price and it indicates that green space is a vital part of urban development in the city area. In conclusion, the green space provides benefits especially regarding its economic value. Thus, conserves and preserve in maintaining this area is ought to be implemented.